Kajian Kebutuhan Luas Lahan Tempat Pengelolaan Tempat Pembuangan Akhir (TPA) Sampah Tipe Sanitary Landfill untuk Sampah di Kota Mataram - Syafri Nazhim; Lina Marta Ningsih; Burhan Azhari (Trends Research of Environmental Studies, 2025)
Urban solid waste management in Mataram City faces serious challenges due to the increasing daily waste generation, which averages 200–220 tons and can rise up to 240 tons per day during certain periods. This study aims to analyze the land area requirements for the final disposal site (sanitary landfill) and to assess the effectiveness of community-based waste reduction programs in extending landfill lifespan. The research applied a descriptive quantitative approach through the collection of primary and secondary data. Primary data were obtained through field observations at the existing landfill site, while secondary data included population size, per capita waste generation, waste composition, and municipal waste management planning documents. Land requirement calculations were conducted using waste generation formulas, population growth projections, and technical factors related to sanitary landfill utilization. The results indicate that household waste separation programs were able to reduce landfill loads by 30–40 tons per day, equivalent to 15–20 percent of total waste generation. This reduction significantly improves land-use efficiency and has the potential to extend the landfill lifespan by 2–3 years beyond the original design plan. The waste composition in Mataram City is dominated by organic waste and plastics in nearly equal proportions, highlighting the need for waste management strategies that prioritize composting and plastic recycling. This study emphasizes that the integration of technical planning and social participation is crucial in developing a sustainable sanitary landfill system in Mataram City.